EXPLORING THE HALAL HORIZON: UNRAVELLING KNOWLEDGE AND PERCEPTIONS ABOUT HALAL MEDICATIONS AMONG PHARMACY UNDERGRADUATES IN MALAYSIA AND INDONESIA - Othman, Mohd Izani; Mohd Najib, Mohd Nadzri; Sulaiman, Suraya; Netti Kemala Sari; Nedita Putri Bandaro; Mohamad Paisal, Muhammad Syamil Fikri; Rusni, Muhammad Fakhrul Fadzli; Jasni, Muhammad Azif; Mohd Isa, Iqmal Fahim (Malaysian Journal of Public Health Medicine, 2025)
The concept of halal medications holds immense significance in Malaysia and Indonesia, where the Muslim population is substantial. As the demand for halal medications continues to rise, it becomes crucial to understand the knowledge and perceptions among pharmacy students regarding the halal aspects. This study explores the significance of halal medications in Malaysia and Indonesia, focusing on final-year Diploma in Pharmacy students. Through a cross-sectional survey, knowledge and perceptions were assessed. Results indicate a positive trend in knowledge levels, with 95.0% of Malaysian and 84.1% of Indonesian respondents scoring excellently or good. Malaysian perceptions were notably positive (mean = 34.50/40), compared to Indonesians (mean = 32.93/40). Both groups expressed favourable attitudes toward halal medications, emphasizing patient rights, transparent labelling, religious respect, public education, and integrating halal topics into the pharmacy curriculum. These findings underscore the importance of educating healthcare professionals, especially pharmacists, on halal medications to enhance patient care in predominantly Muslim nations.